2016
DOI: 10.1111/1471-3802.12230
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Between General and Special Education Teachers in Malaysia

Abstract: Collaboration between general and special education teachers is a necessary component for the successful inclusion of students with a disability in regular schools, but little is known about how well this is working in countries where inclusive education is a recent initiative. This paper reports on the perceptions of special education teachers in Malaysia about their interactions with general education teachers. As part of a larger study, a survey was completed by 48 special education teachers and eight teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Results showed that although special education and general education teachers report maintaining respectful relationships with one another, they report a general disconnect (Khairuddin et al, 2016). For example, special educators reported that they made limited contact with their general education teacher counterparts (Khairuddin et al, 2016).…”
Section: Collaborationmentioning
confidence: 99%
See 4 more Smart Citations
“…Results showed that although special education and general education teachers report maintaining respectful relationships with one another, they report a general disconnect (Khairuddin et al, 2016). For example, special educators reported that they made limited contact with their general education teacher counterparts (Khairuddin et al, 2016).…”
Section: Collaborationmentioning
confidence: 99%
“…This study's focus was to combat the current conditions that prevent collaboration for special educators (Khairuddin, Dally, & Foggett, 2016). Many conversations between special educators and general educators stem from the desire to "fix" a special education student, because of his or her deficits (Candela et al, 2018).…”
Section: Statement Of Purposementioning
confidence: 99%
See 3 more Smart Citations